BCH angles of young female weightlifters during snatch movement - Chiu, H.; Liang, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study is aimed at using the BCH angle which represents the relative movement of lifter's body and barbell to compare the snatch movement of two young female weightlifters. The snatch movements of these two female weightlifters were filmed by a high speed camera (120Hz) and analyzed by Kwon 3D motion analysis software. The BCH angle, defined as the angle between the projection vector of the 7th cervical spinous process to the barbell and the projection vector of the 7th cervical spinous process to the hip joint in the sagittal plane, was calculated. The differences of BCH angles during the whole snatch movement have been found between successful and unsuccessful lifts for S1, and even between successful lifts of S1 and S2. In conclusion, the BCH angle seems to be a simple and good variable to evaluate the snatch techniques of the weightlifters.